2011
DOI: 10.1007/s11064-011-0542-y
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Hydrogen Sulfide is Involved in Asymmetric Dimethylarginine-induced Protection Against Neurotoxicity of 1-Methyl-4-phenyl-pyridinium Ion

Abstract: Asymmetric dimethylarginine (ADMA), an endogenous nitric oxide synthase (NOS) inhibitor, is profoundly protective against 1-methy-4-phenylpyridinium ion (MPP+)-induced neurotoxicity. Reactive oxygen species (ROS) overproduction contributes to the neurotoxicity of MPP+; while hydrogen sulfide (H₂S) is a pivotal endogenous antioxidant. This study is to assess the potential role of endogenous H₂S in the neuroprotection of ADMA against MPP+-induced toxicity in PC12 cells. We showed that ADMA prevented MPP+-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Cardounel and Zweier showed that ADMA protected neurons from NMDA-induced neurotoxicity [ 28 ]. Tang et al demonstrated that ADMA attenuated ROS accumulation in MPP+-treated PC12 cells and protected neurons from MPP+-triggered cell death [ 29 , 30 ]. However, Wang et al reported that exogenous ADMA may induce apoptosis in PC12 cells in a concentration- and time-dependent manner [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cardounel and Zweier showed that ADMA protected neurons from NMDA-induced neurotoxicity [ 28 ]. Tang et al demonstrated that ADMA attenuated ROS accumulation in MPP+-treated PC12 cells and protected neurons from MPP+-triggered cell death [ 29 , 30 ]. However, Wang et al reported that exogenous ADMA may induce apoptosis in PC12 cells in a concentration- and time-dependent manner [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ADMA decrease has been observed also in other neurodegenerative conditions 27 . Moreover, a neuroprotective role for ADMA in Parkinson’s disease has even been suggested 28 .…”
Section: Discussionmentioning
confidence: 99%
“…MPP + was shown to down-regulate CBS expression and activity, thus resulting in decreased H 2 S production in PC12 cells, whereas the improvement of H 2 S levels ameliorated MPP + cytotoxicity and oxidative stress [ 158 ]. Concomitantly, the prevention of oxidative stress, mitochondrial membrane potential loss, cytochrome c release, and decreased Bcl2 expression followed by improved cell viability by asymmetric dimethylarginine in MPP + -exposed PC122 cells was shown to be dependent on CBS expression and subsequent release of H2S [ 159 ], thus being indicative of the beneficial role of H2S in protection against MPP + -induced neuronal apoptosis [ 160 ].…”
Section: Exogenous Neurotoxicantsmentioning
confidence: 99%